The effect of matrix shear strength on the out-of-plane compressive strength of CFRP cross-ply laminates. (15th May 2018) - Yu, B.; Khaderi, S.N.; Deshpande, V.S.; Fleck, N.A.
Abstract: The failure mechanism of 'indirect tension' is explored for cross-ply IM7/8552 carbon fibre/epoxy laminates subjected to quasi-static, out-of-plane compressive loading. The sensitivity of compressive response to strain rate and to the state of cure is measured, motivated by the hypothesis that the out-of-plane compressive strength is sensitive to the matrix shear strength. A pressure-sensitive film is placed between specimen and loading platen, and reveals that a shear lag zone of reduced compressive traction exists at the periphery of the specimen, giving rise to a size effect in compressive strength. The width of the shear lag zone reduces with increasing shear strength of the matrix. The laminates fail by the indirect tension mechanism: out-of-plane compressive loading generates tension in the fibre direction for each ply and ultimately induces fibre tensile failure. Finite element (FE) simulations and an analytical model are developed to account for the effect of matrix shear strength, specimen geometry, and strain rate on the out-of-plane compressive strength. Both the FE simulations and the analytical model suggest a recipe for increasing the through-thickness compressive strength.